Sistem Pakar Analisis Kefungsian Enjin Kereta: MyKERETA - Zulkerneian, Nur Syahirah; Hassan, Norlida (Applied Information Technology And Computer Science, 2021)
The use of cars nowadays has become a necessity to make it easier for a person to move from one destination to another. Basic knowledge of car maintenance and care is very important so that users can enjoy comfort as well as be able to avoid the occurrence of more serious damage. The Car Engine Functional Analysis Expert System (MyKERETA) was developed as an alternative to help car owners know the early symptoms of damage to car engine parts so that they can take early action and subsequently avoid more serious damage. This android-based application is developed based on knowledge engineering methodology and forward chain-based techniques. The editing software uses Android Studio and the JavaScript programming language, as well as MySQL as the database. Therefore, the development of this system is expected to help car users, especially those who still lack knowledge about the car to get initial information on the care of a car as well as diagnose engine damage, thus helping users find out the problem of their car engine failure. In addition, this system is also expected to provide solution suggestions to users and can make it easier for users to store information related to car components that need to be serviced in the future. However, it still requires the services of a skilled mechanic to confirm and repair the damage.